Introducing carbon assimilation in yeasts using photosynthetic directed endosymbiosis - Yang-le Gao; Jay Cournoyer; Bidhan C. De; Catherine L. Wallace; Alexander V. Ulanov; Michael R. La Frano; Angad P. Mehta (Nature Communications)
Abstract Conversion of heterotrophic organisms into partially or completely autotrophic organisms is primarily accomplished by extensive metabolic engineering and laboratory evolution efforts that channel CO2 into central carbon metabolism. Here, we develop a directed endosymbiosis approach to introduce carbon assimilation in budding yeasts. Particularly, we engineer carbon assimilating and sugar-secreting photosynthetic cyanobacterial endosymbionts within the yeast cells, which results in the generation of yeast/cyanobacteria chimeras that propagate under photosynthetic conditions in the presence of CO2 and in the absence of feedstock carbon sources like glucose or glycerol. We demonstrate that the yeast/cyanobacteria chimera can be engineered to biosynthesize natural products under the photosynthetic conditions. Additionally, we expand our directed endosymbiosis approach to standard laboratory strains of yeasts, which transforms them into photosynthetic yeast/cyanobacteria chimeras. We anticipate that our studies will have significant implications for sustainable biotechnology, synthetic biology, and experimentally studying the evolutionary adaptation of an additional organelle in yeast.